Perception of Indonesia and Afghanistan in Preventing Psychic Violence Against the Household Women - Sopacua, Margie Gladies (Jambura Law Review, 2023)
The urgency and purpose of this study examine efforts to prevent psychological violence against women in the household as a form of upholding human rights. The method used is normative juridical, namely by studying theoretical literature, legal concepts, and legal norms, and connected with the efforts to prevent psychological violence against women in the household as a form of upholding human rights. The research results show that prevention psychological violence against women in the household as a form of upholding human rights, namely husbands and wives who are within the scope of the household should further increase their respective faiths by getting closer to God Almighty; Husbands and wives are open to each other, appreciate, respect and love within the scope of the household with full affection so that husbands and wives feel harmonious and comfortable both spiritually, physically, psychologically and so on; We must reject beliefs, beliefs or history about women that women are weak and as a wife if something happens in the household it becomes the wife's fault; Awareness to all parties included in the household sphere that domestic violence that occurs to women as wives is no longer a family disgrace, but acts of domestic violence are criminal acts and need to be handled properly and domestic violence must be abolished in every household sphere ; In order to escape from domestic violence, victims need to get legal protection and safe shelters prepared by the government.